Alabaster. Wolves - Kiernan, Caitlín R. (Dark Horse, 2013)
For nearly as long as she can remember, Dancy Flammarion has fought monsters, cutting a bloody swath through the demons and dark things of the world, aimed like a weapon by forces beyond her control or questioning. But now, for the first time, Dancy finds herself alone--and the wolves are closing in.